Forecasting CEMAC's foreign exchange reserves in presence of unanticipated changes in oil prices: an interrupted time series modelling - Giscard Assoumou-Ella (Journal of Central Banking Theory and Practice, 2019)
The foreign exchange reserves of the Central African Economic and Monetary Community (CEMAC) countries have decreased since the fall of world oil price that began in July 2014. In fact, five of the six of the CEMAC countries are oil producers. Based on interrupted time series modeling, the analysis shows that the unanticipated changes in oil prices immediately led to a decline in the level of their foreign exchange reserves. The trend is also decreasing. The model predicts a continued degradation of these reserves if oil prices remain low. In these conditions, the CEMAC could experience a currency crisis if economic policies implemented in this region do not lead to a return of economic growth.
Keywords: E4; E5; E6; 330; oil prices; CEMAC countries; foreign exchange reserves; interrupted time series analysis.